Peran Kepercayaan Nasabah dalam Memediasi Pengaruh Persepsi Keberkahan terhadap Loyalitas Nasabah Lembaga Keuangan Micro Syariah - Mohamad Mondir; M. Hibatullah Huwaidi (Mazinda : Jurnal Akuntansi, Keuangan, dan Bisnis, 2026)
This study aims to understand how the perception of blessings influences customer loyalty, as well as the role of trust as a mediating variable in this relationship at BMT UGT Nusantara in the Bondowoso region. In the context of Islamic financial institutions, customer decisions are based not only on rational considerations but also on spiritual values believed to bring peace of mind and long-term benefits. This study employs a quantitative approach involving 70 respondents selected through purposive sampling. Data analysis was conducted using the SEM-PLS method with the assistance of the SmartPLS 3 software. The results indicate that the perception of blessings has a positive and significant effect on customer trust and loyalty. Customer trust was also found to have a significant influence on loyalty. Furthermore, trust acts as a mediating variable that strengthens the relationship between the perception of blessings and customer loyalty. This indicates that when customers believe in the presence of blessings in their financial activities, trust grows and fosters stronger loyalty. This study underscores the importance of integrating spiritual values into the strategies of Islamic financial institutions to build long-term relationships with customers